Apakah Komisaris Independen Memoderasi Hubungan Koneksi Politik, Kepemilikan Institusional, Dan Manajemen Laba? - Dyah Aprilia; Yeasy Darmayanti (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to empirically prove the influence of political connections, institutional ownership and independent commissioners on earnings management in non-cyclical consumer sector manufacturing companies listed on the IDX in 2018 - 2022. Methodology/approach: this research uses quantitative methods whose data is obtained from the official website of the Indonesia Stock Exchange (BEI). The method used in sampling was purposive sampling, so that the sample obtained in this research was 17 companies with 85 observation data. The data analysis method used is multiple regression analysis with the help of SPSS version 25 data processing application software. Findings: The results of this study found that the presence of independent commissioners in the company will create tighter and more objective supervision of the financial reporting process so that it will prevent earnings management actions carried out by politically connected managers and with high institutional ownership within the company the institutions will be able to control company and will avoid earnings management practices. Practical and theoretical contributions/Originality: this research provides benefits for related parties such as investors. The results of this research provide new knowledge and insight for investors when they want to invest in a company. With this research, investors are able to assess and analyze a company whether the company is worthy of investment or not. Research limitations: this research has limitations, namely the difficulty in accessing data on each company's website because there are several companies whose data is incomplete. Apart from that, the sample used was too small due to certain criteria so that the sample was limited and the researcher only focused on one sector.